Using verbal and social autopsy approaches to understand why neonates die in rural settings: a case study of a remote rural district in Uganda - Peter Waiswa; Rornald Muhumuza Kananura; Dinah Amongin; Joseph Akuze; Jacquellyn Nambi Ssanyu; Felix Kizito (BMJ Publishing Group, 2024)
Introduction Neonatal mortality remains a formidable challenge in low-resource settings, such as Uganda, despite global health initiatives. This study employs a social and verbal autopsy approach to identify the causes, settings and health accessibility challenges surrounding neonatal deaths in the Luuka district from 1 January 2017 to 31 December 2019.Methods We analysed data from 172 neonatal verbal and social autopsies (VASA) conducted over 3 years, as part of a maternal and neonatal demand and supply health system strengthening intervention. Cause-of-death coding was done by two independent medical officers using WHO-ICD-10 guidelines to ascertain the causes of death. VASA-coded data analysis of the causes of death was done in STATA V.14.0. In addition, 16 key informant interviews were conducted, including 2 community health workers,6 household members and 8 health workers, with qualitative data analysed through thematic content analysis.Results Among the 172 neonate deaths, 95.9% occurred in the early neonatal period (0-6 days) and 4.1% in the late neonatal period (7-27 days). The primary causes of death were birth asphyxia (42.4%), low birth weight/prematurity (18.6%), other perinatal causes (12.8%) and neonatal sepsis (9.3%). Delays in getting appropriate care at the facility (delay 3) and delays in seeking care (delay 1) (51.2% and 44.2%, respectively) were linked to newborn mortality. Qualitative insights underscored inadequate awareness of neonatal danger signs, deficient referral systems, drug shortages, reliance on unskilled traditional birth attendants and insufficient neonatal care facilities as significant contributors.Conclusion Addressing delays in both home-based care (delay 1) and timely access to appropriate care in healthcare facilities (delays 2 and 3) is pivotal in mitigating neonatal mortality. Comprehensive interventions targeting improved access to maternal services and enhanced quality of care in health facilities are imperative for advancing newborn survival in rural settings.